2016
DOI: 10.3390/ijms17081365
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Alleviates Liver Apoptosis in Bile Duct Ligation Young Rats

Abstract: Bile duct ligation (BDL)-treated rats display cholestasis and liver damages. The potential protective activity of melatonin in young BDL rats in terms of apoptosis, mitochondrial function, and endoplasmic reticulum (ER) homeostasis has not yet been evaluated. Three groups of young male Sprague-Dawley rats were used: one group received laparotomy (Sham), a second group received BDL for two weeks (BDL), and a third group received BDL and intraperitoneal melatonin (100 mg/day) for two weeks (BDL + M). BDL group r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 42 publications
1
5
0
1
Order By: Relevance
“…Knockdown of Y1 receptor attenuated the inhibitory effects of Dex on the proliferation ability of MC3T3-E1 cells (Figure 2D). Activation of caspases has been shown to contribute to apoptosis in various types of cells [21,22]. Thus, we evaluated cell apoptosis by detecting the levels of cleaved caspase 3 and cleaved caspase 9, two key molecules involved in apoptosis process.…”
Section: Resultsmentioning
confidence: 99%
“…Knockdown of Y1 receptor attenuated the inhibitory effects of Dex on the proliferation ability of MC3T3-E1 cells (Figure 2D). Activation of caspases has been shown to contribute to apoptosis in various types of cells [21,22]. Thus, we evaluated cell apoptosis by detecting the levels of cleaved caspase 3 and cleaved caspase 9, two key molecules involved in apoptosis process.…”
Section: Resultsmentioning
confidence: 99%
“…An important finding of our study is the degenerative changes in the later stages of the experiment of the muscular membrane of the wall of the common bile duct. Experiments have shown that damage to the muscular layer of the bile duct leads to the development of liver cirrhosis [16,19,28,33] and even hepatocellular carcinoma [1,30]. Significant collagen deposition, portal fibrosis, periductal edema, lymphocytic inflammation, dilatation of all bile ducts, blind end of small bile ducts, cholestasis (bile corks), increased systemic oxidative stress, and fibrosis were observed in rats after ligature was applied to the common bile duct, which eventually leads to liver cirrhosis [15,32].…”
Section: Discussionmentioning
confidence: 99%
“…1). BDL-induced liver fibrosis is accompanied by hepatocytes apoptosis which is an important feature of liver injury 22,23 . However, the number of apoptotic cells marked by TUNEL fluorescence staining in nonfibrotic regions of the fibrotic liver tissue was evidently decreased in following therapeutic treatment with roseotoxin B ( Fig.…”
Section: Roseotoxin B Therapeutically Improved Bile Duct Ligation (Bdmentioning
confidence: 99%